Peripheral intrahepatic cholangiocarcinoma (cip) - Keuchkerián, Marcel; Hernández, Nelia; Sanguinetti, Julio (Cirugía del Uruguay, 2003)
Pepheral intrahepatic cholagiocarcinoma (PIC) is an adenocarcinoma which has developed from the epithelium of sma/1 bife ducts. lt represents approximately from 3% to 5% of primitive liver tumors. lts maximum incidence is from age 50 onas. lt has we/1-deined geographic distribution, being the most frequent liver tumor in sone Asian countries. lts onset is favored by certain intrahepatic lithiasis pathologies, Caroli's disease, sclerosing cholangitis, inlammatory colitis, exposure to Thorotrasf and sone parasitosis. In man y of these we propase as lesion mechanism, biliary stasis and infection which /ead to biliay displasia and final/y to carcinoma.